1976
DOI: 10.1002/1097-0142(197612)38:6<2583::aid-cncr2820380652>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis from prostatic carcinoma

Abstract: Between 1959 and 1971 there were 91 patients with clinically diagnosed prostatic carcinoma who were autopsied at Roswell Park Memorial Institute. In four of these 91 (4.4%) intracerebral metastasis were found at autopsy, but only in one of these four was the diagnosis arrived at pre-mortem. This report describes the diagnosis and management of intracerebral metastasis from prostate carcinoma. It appears, on the basis of our initial experience, that the clinical diagnosis of this entity deserves more frequent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0
4

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 24 publications
4
28
0
4
Order By: Relevance
“…Estimates of the frequency of brain metastasis reported in autopsy series vary from 1% to 6% in patients with a premortem diagnosis of prostate carcinoma, but the true incidence may be 2-10 times greater. [1][2][3][4][5] In this retrospective study of patients with prostate carcinoma, we estimated the incidence of parenchymal CNS metastasis, examining the clinical characteristics and the effects of treatment, histology, location of metastases, and neuroimaging tests on survival.…”
mentioning
confidence: 99%
“…Estimates of the frequency of brain metastasis reported in autopsy series vary from 1% to 6% in patients with a premortem diagnosis of prostate carcinoma, but the true incidence may be 2-10 times greater. [1][2][3][4][5] In this retrospective study of patients with prostate carcinoma, we estimated the incidence of parenchymal CNS metastasis, examining the clinical characteristics and the effects of treatment, histology, location of metastases, and neuroimaging tests on survival.…”
mentioning
confidence: 99%
“…Even as the second most common cancer worldwide, prostate cancer rarely metastasizes to the brain, with only 0.2–0.6% of such cases (9,2729). In general, central nervous system involvement is restricted to the spine, involving the perineural and capsular lymphatic system, as well as Batson's venous plexus (29).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the data concerning the incidence of brain metastases come from occasional reports or large autopsy series because they were usually asymptomatic in living patients and discovered only incidentally after death [13]. The first retrospective study was published in 1976 by Catane et al, who found an incidence of 4.4% in 91 patients with prostate carcinoma [16]; in 1984, Taylor et al reported that intracranial metastases had been found in 14 out of 126 autopsies (11.1%) performed between 1954 and 1981 [17].…”
Section: Discussionmentioning
confidence: 99%